Inelastic Electron Scattering Form Factor of Isoscalar (T = 0) and Isovector (T = 1) Particle-hole States in 12C and 16O - Hassan, S.A.; Abusini, Majid; Al-Sa’ad, A.A. (Ukrainian Journal of Physics, 2022)
Inelastic longitudinal and transverse electron scattering form factors of low-lying T = 0, T = 1 particle-hole states of 12C and 16O are studied in the framework of the Tamm–Dancoff approximation (TDA). The Hamiltonian with the Michigan-three-Yukawa (M3Y) potential is diagonalized. To obtain a good agreement with the experimental data, the ground state is corrected by including the admixture from higher orbits with regard for the core polarization effects.